2006
DOI: 10.1007/s00262-006-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell based antitumor vaccination: impact of functional indoleamine 2,3-dioxygenase expression

Abstract: The presented observations suggest a potential clinical relevance of IDO expression in DC-based therapeutic vaccines via the attraction or induction of FoxP3(+) T-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…Our data show that activated T cells can induce IDO expression in tumor cells and negatively impact the immune response. In melanoma, it has been demonstrated that IDO can affect DC-based vaccines given that IDO-positive cells were detected by immunohistochemistry in tumor biopsies 24 h after the administration of a DC-based vaccine (48). Furthermore, IDO expression led to increased expression of FoxP3, and thus possibly T regulatory T (Treg) cells (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that activated T cells can induce IDO expression in tumor cells and negatively impact the immune response. In melanoma, it has been demonstrated that IDO can affect DC-based vaccines given that IDO-positive cells were detected by immunohistochemistry in tumor biopsies 24 h after the administration of a DC-based vaccine (48). Furthermore, IDO expression led to increased expression of FoxP3, and thus possibly T regulatory T (Treg) cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, it has been demonstrated that IDO can affect DC-based vaccines given that IDO-positive cells were detected by immunohistochemistry in tumor biopsies 24 h after the administration of a DC-based vaccine (48). Furthermore, IDO expression led to increased expression of FoxP3, and thus possibly T regulatory T (Treg) cells (48). The complementarities between these two immunosuppressive mechanisms have been demonstrated recently by Munn and colleagues (49) as they showed that IDO-expressing plasmacytoid DC can activate resting Treg in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Following vaccination an accumulation of IDO-expressing DCs and regulatory T cells was observed at the injection site. All patients had a rapid progressive disease and a short overall survival (35).…”
Section: Discussionmentioning
confidence: 99%
“…adjuvants like TLR9 agonist CpG (Mellor et al, 2005;Wingender et al 2006). Moreover, it was reported by Wobser et al (2007) that the use of IL-1b, TNF, IL-6, and PGE 2 to stimulate in vitro DC generation resulted in upregulation of IDO expression in DC. On the other hand, inhibition of IDO activity by small molecules analogous to tryptophan, like 1-MT, elicited anti-tumor responses in experimental animal models and enhanced the effects of chemotherapy.…”
Section: Ido-dcmentioning
confidence: 99%